The young H.G. Wells : changing the world - Tomalin, Claire (Penguin Press, 2021)
The acclaimed literary biographer looks at the early life of influential writer and public figure H.G. Wells, from his school days and his emergence as writer of extraordinary depth to the publication of The Time Machine.